A Partitioned Global Address Space implementation of the European Centre for Medium Range Weather Forecasts Integrated Forecasting System. (August 2015) - Mozdzynski, George; Hamrud, Mats; Wedi, Nils
Today the European Centre for Medium Range Weather Forecasts (ECMWF) runs a 16 km global T1279 operational weather forecast model using 1536 cores of an IBM Power7. Following the historical evolution in resolution upgrades, the ECMWF could expect to be running a 2.5 km global forecast model by 2030 on an exascale system that should be available and hopefully affordable by then. To achieve this would require the Integrated Forecasting System (IFS) to run efficiently on about 1000 times the number of cores it uses today. In a step towards this goal, the ECMWF have demonstrated the IFS running a 10 km global model efficiently on over 40, 000 cores of HECToR a Cray XE6 at the Edinburgh Parallel Computing Centre. However, getting to over a million cores remains a formidable challenge, and many scalability improvements have yet to be implemented. The ECMWF is exploring the use of Fortran2008 coarrays; in particular, it is possibly the first time that coarrays have been used in a world-leading production application within the context of OpenMP parallel regions. The purpose of these optimisations is primarily to allow the overlap of computation and communication, and further, in the semi-Lagrangian advection scheme, to reduce the volume of data communicated. The importance of this research is such that if these and other planned developments are successful, the IFS model may continue to use the spectral transform method to 2030 and beyond on an exascale-sized system. The current status of the coarray scalability developments within the IFS are described together with a brief outline of future developments.